A Proactive Approach to the Translation of Bible Stories for Children - Beard, Luna; du Toit, Jaqueline (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis paper presents cognitive poetics as an agent in overcoming difficulties in translating bible stories for young children in the multi-lingual and multi-cultural South African environment. The translated picture book texts typically involve the integration of words with pictures. For the purposes of this article, the Genesis 28 narrative of Jacob’s dream in the Hebrew source text is compared in various South African translations. Religious literature was chosen as subject matter because of the relative certainty of comparative translations in most of the eleven official languages of South Africa, but the present article is limited mainly to English and Afrikaans translations. The analysis is done within the fairly new framework of cognitive poetics, which combines psychological and cognitive linguistic approaches to the study of literature. The focus is on the contribution of cognitive linguistics to the translation of children’s literature, in the spirit of proactive translatology.